Determinants of Future Microbial Food Safety in Canada for risk communication. Issue 3 (15th January 2015) - Charlebois, Sylvain; Summan, Amit
Abstract This paper investigates the factors that are affecting food safety in Canada today, and those that will become increasingly important in the future. The tools used to complete this analysis are primarily the review of scientific and "gray" literature, and the analysis of multiple sources of data. We develop a methodology for ranking the factors and rank the factors according to their predicted effect on foodborne disease in Canada. The analysis reveals the top three factors that will be detrimental to food safety as pathogen evolution, increase in temperatures and increase in extreme weather events. Future studies may benefit from an analysis of factors by commodity. Practical Applications Food regulatory bodies, such as the Canadian Food Inspection Agency, have a finite number of resources to address emerging food safety risks. A framework for ranking factors effecting food safety discussed in this paper will help determine the optimal distribution of resources designated for preventative and mitigative food safety programs and can better assist food regulators in anticipating emerging systemic risks. Although the focus of this paper is on the Canadian context, many of the results may be applied to other Western countries.